Successful use of antihistamines in severe hypereosinophilia - Stefano Vallero; Anna Mondino; Loredana Farinasso; Giulia Ansaldi; Mirella Davitto; Ugo Ramenghi (MDPI AG, 2012)
Eosinophilia is common in childhood, and in most cases it is mild and of limited clinical relevance, being often secondary to allergy or infections. In rare cases, eosinophilia may be idiopathic or related to neoplastic aetiology. When severe and protracted, it can cause potentially irreversible organ or system damage, whose prevention is the first priority in the clinical management of hypereosinophilia. We describe the case of a patient with very severe eosinophilia, in whom antihistamines proved to be effective and safe in contributing to the eosinophil count normalization, thus avoiding the use of steroids until the hypothesis of an underlying neoplastic disorder was reasonably excluded.